“Construcción de un generador de acetileno para la suelda autógena” en la escuela de educación técnica, facultad de CIencias de la Educación Humanas y Tecnologías de la Universidad Nacional de Chimborazo, periodo académico octubre 2015 – febrero 2016. - Shagñay Pérez, Dennys Marcelo (2016)
Welding has made us increasingly easy joining metals, thus having different processes to unite them, such as electric arc welding, MIG welding, MAC, ICT, spot welding and weld welding course. One of the advantages of oxyacetylene welding is to facilitate the transport and perform welding work anywhere. The operating principle of the autogenous welding is to achieve a flame combining two gases, oxygen and acetylene, which goes at high speed by a blowtorch at a temperature approximating 3500 °C, this flame will be responsible for melting and piecing together. One of the components for this process is acetylene gas, and is achieved by reacting the carbide with the water, so it will be necessary to have a generator. To avoid high costs when buying a generator, it is possible to build and this must necessarily have a pre-construction design as there are designs as needed and / or tastes of the manufacturer, after having the desired design proceeds with construction plans of each of the parts of the generator, they must be precise because it depends on each piece have exact measurements to form part of a set, having the designed levels will continue with the construction of each parts that constitute the generator and the cylinder, tank tops carbide, debugger, etc. The construction will have to be ruled to the designs of the planes both in measures and in material of construction. Finally and possessing all the constructed pieces it will begin with the assembly of the same ones to form train the generator according to the design. In conclusion, it is possible to construct a generator providing that the order and procedure are respected for the process of construction before detailed and there is had the basic necessary knowledge on the different technologies such as welding, metal lathing, cutting and modification of the shape of the metal between others, all the processes stepwise are detailed in this document that can serve as support.